Indonesian Tuna Economic Performance in the International Market - Purimahua, Sarlotha Yulliana; Tupamahu, Yonette Maya (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2022)
The purpose of this research is to analyze the factors that influence the economic performance of Indonesian tuna and to analyze the contribution of the economic performance of Indonesian tuna to the international market. This research was limited to skipjack tuna (Katsuwonus pelamis). Analysis of the simultaneous equation model of Indonesian tuna economic performance is divided into: a) The Indonesian Market Block, including Indonesian Tuna Supply, Indonesian Tuna Demand, Indonesian Tuna Price, and b) International Market Block, including World Tuna Price, World Tuna Demand, and World Tuna Supply. Statistical criteria that must be met: test the coefficient of determination (R2), F test, and t test. Econometric criteria include: stationarity test, normality test, autocorrelation test, multicollinearity test, and heteroscedasticity test. The results of research on the factors that influence the economic performance of tuna in the Indonesian market are: a). The amount of supply for Indonesian tuna production is affected by the price of Indonesian tuna in year t. b) The amount of demand for tuna exports is affected by the price of Indonesian tuna in year t, the rupiah exchange rate against the US dollar in year t and world tuna prices in year t. c) The price of Indonesian tuna is influenced by the population of Indonesia in year t and the price of Indonesian tuna in the previous year has a significant and negative relationship to the price of Indonesian tuna in year t.